Psoriasis and its impact on in-hospital outcome in patients hospitalized with acute kidney injury - Wild, Johannes; Hobohm, Lukas; Münzel, Thomas; Wenzel, Philip; Steinbrink, Kerstin; Karbach, Susanne; Keller, Karsten (Journal of Clinical Medicine, 2020)
Background: Psoriasis is a chronic inflammatory disease which affects the body far beyond the skin. Whereas there is solid evidence that chronic skin inflammation in psoriasis drives cardiovascular disease, the impact on renal impairment and acute kidney injury (AKI) is still unclear. We aimed to analyze the impact of psoriasis on the in-hospital outcome of patients hospitalized with AKI. Methods: In this retrospective database study, we investigated data on characteristics, comorbidities, and in-hospital outcomes for all hospitalized patients with AKI stratified for concomitant psoriasis, which were collected by the Federal Office of Statistics in Germany between 2005 and 2016. Results: Among the 3,162,449 patients treated for AKI in German hospitals between 2005 and 2016, 11,985 patients (0.4%) additionally suffered from psoriasis. While the annual number of AKI patients with psoriasis increased significantly from 485 cases (4.0%) in 2005 to 1902 (15.9%) in 2016 (p < 0.001), the in-hospital mortality decreased substantially (from 24.9% in 2005 to 17.4% in 2016; p < 0.001). AKI patients with concomitant psoriasis were younger (70 (IQR; 60–78) vs. 76 (67–83) years; p < 0.001) and were more often treated with dialysis (16.3% vs. 13.6%, p < 0.001). Presence of psoriasis in AKI patients was associated with reduced prevalence of myocardial infarction (OR 0.62; p < 0.001), stroke (OR 0.85; p = 0.013), and in-hospital mortality (OR 0.75; p < 0.001). Conclusions: AKI patients with psoriasis were hospitalized in median 6 years earlier than those without. Despite younger age, we detected higher use of kidney replacement therapy in patients with psoriasis, indicating a more severe course of AKI. Our findings might improve management of these patients and contribute evidence for extracutaneous, systemic manifestations of psoriasis.
Gesehen am 24.11.2020